Acute Stroke Imaging Research Roadmap IV: Imaging Selection and Outcomes in Acute Stroke Clinical Trials and Practice. Issue 8 (August 2021) - Campbell, Bruce C.V.; Lansberg, Maarten G.; Broderick, Joseph P.; Derdeyn, Colin P.; Khatri, Pooja; Sarraj, Amrou; Saver, Jeffrey L.; Vagal, Achala; Albers, Gregory W.
Abstract : Background and Purpose: The Stroke Treatment Academic Industry Roundtable (STAIR) sponsored an imaging session and workshop during the Stroke Treatment Academic Industry Roundtable XI via webinar on October 1 to 2, 2020, to develop consensus recommendations, particularly regarding optimal imaging at primary stroke centers. Methods: This forum brought together stroke neurologists, neuroradiologists, neuroimaging research scientists, members of the National Institute of Neurological Disorders and Stroke, industry representatives, and members of the US Food and Drug Administration to discuss imaging priorities in the light of developments in reperfusion therapies, particularly in an extended time window, and reinvigorated interest in brain cytoprotection trials. Results: The imaging session summarized and compared the imaging components of recent acute stroke trials and debated the optimal imaging strategy at primary stroke centers. The imaging workshop developed consensus recommendations for optimizing the acquisition, analysis, and interpretation of computed tomography and magnetic resonance acute stroke imaging, and also recommendations on imaging strategies for primary stroke centers. Conclusions: Recent positive acute stroke clinical trials have extended the treatment window for reperfusion therapies using imaging selection. Achieving rapid and high-quality stroke imaging is therefore critical at both primary and comprehensive stroke centers. Recommendations for enhancing stroke imaging research are provided.